A Framework to Support Improvements to First Nation Education - Bressette, Arielle (Scholarship@Western, 2022)
During the 2022 Indigenous Head and Heart Fellowship at Western University, working with Dr. Brent Debassige and the First Nations with Schools Collective, I developed this framework to support improvements in First Nation education. I have used the 6 R's framework to summarize the project's key findings that entailed online webinars in which members could extensively discuss First Nation education enhancement. These 6 R's include Respect, Refusal, Relationality, Relevance, Responsibility, and Reciprocity. The 6 R's closely tie aspects like effective leadership, robust policies, and culture to the progress of First Nation education. This project's principal conclusion is that equitable funding levels are central to the efforts aimed at improving all aspects of First Nation education.